Oman's Ability to Attract FDI: Dunning Instrument Survey Analysis - Bait Ali Sulaiman, Mohammed Ali (2020)
The purpose of this paper is to establish the extent to which Oman is capable of attracting more of the foreign direct investment (FDI) through dunning model instruments. The results of the analysis are determined using responses provided by the foreign companies concerning the features of Oman. Data used in the analysis were collected from 30 different foreign companies operating in Dhofar region of Oman using questionnaires. ANOVA test, Chi-square tests and Friedman's mean ranks were carried out to test the homogeneity and magnitude of the responses given by the respective companies. the findings of Effect size analysis indicate that Oman’s system structure, Policy framework, provision of facilities and ease of access are strongly contributing in attracting FDI. However, Oman needs to focus on the improvement of business friendly environment and compassionate policy formation in favor of investors.